Characterization of football injuries: A retrospective study with athletes from a Brazilian championship - Nunes, B. E. B. R.; Gama Filho, A. C. B.; Manso, G. J. M. C.; Ferreira, M. D. A.; de Souza, C. D. F.; Júnior Cunha, A. T. (Science & Sports, 2023)
Background Football players, due to the characteristics of sports activity, are constantly exposed to the occurrence of musculoskeletal injuries. This study aimed to describe the profile in professional athletes from Alagoas, Brazil, participants in the Alagoas` First Division Championship of 2020.